The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf00116316
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific diversity of the Cassava Green Mite Mononychellus progresivus (Acari: Tetranychidae) using comparisons of mitochondrial and nuclear ribosomal DNA sequences and cross-breeding

Abstract: Navajas, M., Gutierrez, J., Bonato, O., Bolland, H.R. and Mapangou-Divassa, S., 1994. lntraspecific diversity of the Cassava Green Mite Mononycheltus progresivus (Acari: Tetranychidae) using comparisons of mitochondrial and nuclear ribosomal DNA sequences and cross-breeding. Exp. Appl. Acarol., 18: 351-360.lntraspecific diversity in Cassava Green Mite Motwnychellus progresivus Doreste was examined using individuals collected in Benin and the Congo and in Columbia and Brazil. Comparisons were based on mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
70
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 25 publications
13
70
1
6
Order By: Relevance
“…For example, Navajas et al (1998 found very low variation in ITS-2 sequences within Tetranychus urticae. Similar patterns of variation were found by Navajas et al (1994) for Mononychellus progresivus and, as mentioned above, by Zahler et al (1999) and Berrilli et al (2002) for Sarcoptes. In addition, Zahler et al (1998) and Essig et al (1999) were not able to find clear differences within the worldwide distributed genera Psoroptes and Chorioptes, respectively.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For example, Navajas et al (1998 found very low variation in ITS-2 sequences within Tetranychus urticae. Similar patterns of variation were found by Navajas et al (1994) for Mononychellus progresivus and, as mentioned above, by Zahler et al (1999) and Berrilli et al (2002) for Sarcoptes. In addition, Zahler et al (1998) and Essig et al (1999) were not able to find clear differences within the worldwide distributed genera Psoroptes and Chorioptes, respectively.…”
Section: Resultssupporting
confidence: 87%
“…The number of variable sites was very different among populations: the population ItNWVv was the most variable (30 mutations), whereas the ItNWMf (4 mutations) and SpNEVv (5 mutations ITS-2 rDNA appears to be suitable genetic marker for distinguishing closely related species and examining phylogenetic relationships within genera but not suitable for genetic characterization within a species for mites (Navajas et al, 1994(Navajas et al, , 1998Navajas and Fenton, 2000;Zahler et al, 1998Zahler et al, , 1999Essig et al, 1999;Berrilli et al, 2002). For example, Navajas et al (1998 found very low variation in ITS-2 sequences within Tetranychus urticae.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the molecular genetics of this group of sand flies (Esseghir et al, 1997;Ready et al, 1997Ready et al, , 1998Ishikawa et al, 1999). However, studies of the molecular phylogenetics of other arthropod groups suggest that sequence from region I of the mitochondrial cytochrome c oxidase I (COI) gene might be informative for clarifying Lutzomyia taxonomy at the species level (Navajas et al, 1994(Navajas et al, , 1996(Navajas et al, , 1998Roderick and Gillespie, 1998). Here, we present a phylogeographical interpretation of L. longipalpis based on molecular phylogenetic analysis using mtDNA and available theories on the historical physical geography of Central and South America (Haffer, 1969;Howe, 1974;Keigwin, 1978;Haffer, 1981;Rod, 1981;Sykes et al, 1982;Stehli and Webb, 1985;Hoorn, 1994;Hoorn et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the coastal and cool upper midland zones, predacious mites suppressed the pest mite density to below injury levels (Mutisya et al, 2015). Gutiérrez (1987) Navajas et al (1994) showed complete similarity of the genomic characteristics of different African populations of CGM to those of Colombia; whereas the populations from Brazil (South America) were found to be different. Tetranychid species diversity has been reported since the last century (Boudreaux, 1963;Navajas et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Gutiérrez (1987) Navajas et al (1994) showed complete similarity of the genomic characteristics of different African populations of CGM to those of Colombia; whereas the populations from Brazil (South America) were found to be different. Tetranychid species diversity has been reported since the last century (Boudreaux, 1963;Navajas et al, 1994). reported acaricide abamectin resistance by the red tomato mite, Tetranychus evansi Pritchard & Baker in Asian countries, where species intrageographical variations were evident among the populations on ITS and COI regions.…”
Section: Introductionmentioning
confidence: 99%